Welfare implications on management strategies for rearing dairy calves: A systematic review. Part 2 – Social management - Carulla, Patricia; Villagrá, Arantxa; Estellés, Fernando; Blanco-Penedo, Isabel (Frontiers in Veterinary Science, 2023)
Raising a healthy calf up to puberty is essential for optimal farm performance. It is therefore, it is necessary to promote animal welfare from the three spheres during this short period. Social management has been postulated as essential in lowering stress and consequently improving calf welfare during this period. Only the health sphere has been studied for a long time, but more recent studies have recently promoted positive experiences and emotional states from affective states or cognitive judgment and natural living spheres. A systematic review of different management strategies in rearing dairy calves according to the three spheres of animal welfare has been conducted using an electronic search strategy. The analysis and extraction of information from studies were performed according to a protocol. From 1,783 publications screened, only 351 met the inclusion criteria. The publications identified in the search can be divided into two main groups, feeding and social management, based on the main topic of the publication. This review provides an overview of social management, understood as the calf's interaction with others around it. Primary social management issues that emerged were social housing with congeners, separation from the mother and human-animal interaction, distributed in the three broad spheres of animal welfare. The review highlights unresolved questions about how social management practices affect the three spheres of animal welfare at this life stage and the need to standardize good socialization practices for this stage. In conclusion, all the information shows that social housing has improved animal welfare from affective states, cognitive judgment, and natural living spheres. However, gaps in research were identified in relation to the optimal time to separate the calf from the mother, the optimal time to group with conspecifics after birth and group size. Further research on positive welfare through socialization are needed.